Bakanae Disease - A Serious threat to Basmati Rice Production in India - Singh, Vikram; Kapoor, Promil; Kumar, Ashwani (Journal of Cereal Research, 2025)
Bakanae disease caused by Fusarium fujikuroi Nirenberg has been reported from nearly all rice-growing countries across the world, and it has become a serious threat issue in Asian countries. The disease incidence is especially high on the varieties Pusa Basmati 1121 and Pusa Basmati 1509, which are gaining popularity throughout the country, particularly in Punjab and Haryana due to its superior grain quality. It is responsible for high yield losses ranging from 3.0-95.4% and its prevalence varies depending on the region and cultivars used. The typical and distinguished symptoms of the disease are elongation and rotting of rice plants. This disease is seed borne and soil borne in nature and become more prevalent in rice-growing areas around the world in recent years. Seed treatment with fungicides is currently the most important disease management approach utilized worldwide. A systematic study of how the disease develops under the influence of variable climatic conditions is necessary to manage this emerging disease efficiently, and good management measures can help us conquer it in the future.